The personality of Lavrovskyi M.O. in the education space of Kharkov University - Farbak, Tetiana (Continuing Professional Education: Theory and Practice, 2019)
Lavrovskyi M.O. – a pedagogue, a scholar, an education reformer of the nineteenth century. Lavrovskyi’s activity at Kharkiv University is mentioned in the works of Bahalii D.I., Halanskyi M.G., Budilovych A.S., Sumtsov M.F. The articles of Kulish S.M., Dolapchi A.Y., Astakhova V.I., Timchenko A.M., Yurchenko L.P. and others belong to modern research. This article investigates some areas of management, scientific and educational activities of the scientist in Kharkov Imperial University. We found the fact of the impact of becoming a famous scientist and linguist Potebnia O.A. In his memoirs, namely Lavroskyi M.O. was the first to propose to read him “Thoughts about the history of the Ruthenian language”, a book of Sreznevskyi I.I. that influenced the further research of the scientist. The paper provides information on the public lecture, dedicated to the memory of Shevchenko T.G. Actually Lavrovskyi M.O. was one of three professors (others are Sokal I.P. and Zernin O.P.) who had been already advocated public lectures in memory of Taras Shevchenko in the first anniversary of the death of the Kobzar. The article reveals the scientist’s opinion on setting a monument to Karazin V.N. in Kharkov and the information on scientific activities for the improvement of teaching in public schools of Kharkiv school district. Thus, in our view, Lavrovskyi M.O. was a talented and accommodating manager, who took into account and respected the views of his colleagues and students. He was progressive in his thoughts and actions. Besides, he was always being the focus of secondary school teachers and the public